THE ACCURACY MEASUREMENT OF HARDWARE TOOLS METROLOGICAL CHARACTERISTICS FOR SPECTRAL FRACTIONS SIGNAL IDENTIFICATION - Kharchenko, Volodymyr; Larin, Vitaliy; Savitskaya, Iana (Proceedings of National Aviation University (archive), 2014)
The article gives the accuracy figures quantitative assessment by the example of hardware toolsbasic main metrological characteristics determination, which allows provide the trustworthiness of signals spectralcomponents in the real time mode. The influence of random error fractions is automatically taken into account.